UWB antenna using indium tin oxide (ITO) - Abdul Latif, Nadiyatul Akmar (2014)
Recently, the need of high data rate communication, enormously fast speed and shorter distance, the engineers and scientists had have decided to work in the larger scale of frequency resulted in the usage of ultra wide band (UWB) frequency which ranged from 3.1 GHz to 10.6 GHz. The patch antennas offer a potential solution for narrowband and with some modifications and researches done before, it does applicable for the ultra-wide band applications. It cost, light weight, easy to feed and their attractive radiation characteristics. In this project, the performance of the UWB antenna characteristics using Indium Tin Oxide (ITO) and AgHT were investigated. Parametric studies were performed to quantify the effect of the ITO and AgHT characteristics as well as the PET (plastic polymer) coating. All those parametric studies are conducted and simulated using CST Microwave Studio. The reflection coefficient, radiation pattern, VSWR and gain values were compared and contrast between the two antennas. It can be concluded that the AgHT coated antenna works better than ITO in terms of the gain and radiation pattern while work as good as ITO in reflection coefficient and VSWR